Influence Of Farmersa Group Cohesion On Adoption Of Climate Change Adaptation Strategies In Delta State, Nigeria (Global Journal of Science Frontier Research, 2012)
This study was conducted to assess the influence of farmers' group cohesion on climate change adaptation measures in Delta State, Nigeria. Data for the study were collected from 143 arable crop farmers drawn from the three agricultural zones of the state. Data were collected with the use of descriptive and inferential statistics. Most of the farmers subscribed to groups for access to extension service and credit facilities. The various groups were cohesive and the level of adoption of climate change adaptation strategies was high. Group cohesion influenced the high level of adoption of climate change adaptation methods .The major barriers to adaptation to climate change were lack of money and scarcity of technologies. It was recommended that farmers should be encouraged to continue to subscribe to farmers' group and should be given credit through the groups by the government and more technologies on climate change adaptation should be transferred to farmers.
Keywords: group cohesion; climate change; adaptation; prevention motivation theory